2022
DOI: 10.3389/fchem.2021.805654
|View full text |Cite
|
Sign up to set email alerts
|

Designing New Material Based on Functionalized Multi-Walled Carbon Nanotubes and Cu(OH)2–Cu2O/Polypyrrole Catalyst for Ethanol Oxidation in Alkaline Medium

Abstract: In this work, copper(II) hydroxide (Cu(OH)2) and copper oxide (Cu2O) nanostructures are deposited on functionalized multi-walled carbon nanotubes/polypyrrole to report an efficient electrocatalyst for ethanol oxidation in alkaline medium. In the first step, the deposition of functionalized multi-walled nanotubes of carbon (F-MWCNTs) on the electrode surface was carried out using drop casting mode followed by the electrodeposition of polypyrrole (PPy) and copper nanoparticles (Cu-Nps) using galvanostatic mode. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…In addition to this, two other bands were noticed at 976 and 1741 cm −1 , which are attributed respectively to the C=O and C-O of the -COOH. Another band was observed at 3600 cm −1 indicating the presence of the hydroxylic group -OH of -COOH ( Oularbi et al, 2017 ; Oularbi, 2018 ; El Attar et al, 2022 ). These results demonstrated that the MWCNT were successively functionalized.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, two other bands were noticed at 976 and 1741 cm −1 , which are attributed respectively to the C=O and C-O of the -COOH. Another band was observed at 3600 cm −1 indicating the presence of the hydroxylic group -OH of -COOH ( Oularbi et al, 2017 ; Oularbi, 2018 ; El Attar et al, 2022 ). These results demonstrated that the MWCNT were successively functionalized.…”
Section: Resultsmentioning
confidence: 99%
“…[38,39]. The mechanism of ethanol oxidation with regard to catalysts based on copper particles according to Reactions ( 5)-( 8) looks like [40]:…”
Section: Electrochemical Study Of Synthesized Particles In Ethanol Ox...mentioning
confidence: 99%
“…The two curves describe a semicircle and a straight line. In general, the semicircle in the higher frequency is characteristic of the highest charge transfer resistance and the straight line at low frequency is due to the diffusion limiting process [22]. The charge transfers resistance (Rct) of the bare carbon paste electrode and the carbon paste electrode modified with poly(EBB R) are 15 kΩ and 5 kΩ, respectively.…”
Section: Characterization By Electrochemicalmentioning
confidence: 99%